2015
DOI: 10.1179/2045772315y.0000000059
|View full text |Cite
|
Sign up to set email alerts
|

Surface electromyography as a measure of trunk muscle activity in patients with spinal cord injury: a meta-analytic review

Abstract: This systematic review evaluated the value of trunk muscles for patients with SCI. We recommend use of SEMG as an assessment tool for improving the comparability and interpretability of trunk muscle activity of SCI therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
1
14
1
1
Order By: Relevance
“…MA during lying and sitting is similar in both groups. Another study found significant higher EMG activity levels in static trunk muscles in individuals with SCI relative to healthy controls during tasks like sitting [32]. The present study did not find a difference between the ambulatory groups, possibly due to the muscle groups measured (mostly leg and back muscles instead of trunk muscles per se).…”
Section: Discussioncontrasting
confidence: 69%
“…MA during lying and sitting is similar in both groups. Another study found significant higher EMG activity levels in static trunk muscles in individuals with SCI relative to healthy controls during tasks like sitting [32]. The present study did not find a difference between the ambulatory groups, possibly due to the muscle groups measured (mostly leg and back muscles instead of trunk muscles per se).…”
Section: Discussioncontrasting
confidence: 69%
“…2 and 3) supports the view that clinically detectable sensory input from the lower limbs to the supraspinal structures was not required to achieve full weight-bearing standing without external assistance, and that sensory information projected to the human spinal circuitry plays a primary role in promoting motor patterns sufficient for standing. On the other hand, the lower neurological level of injury in the two individuals graded A compared with the two graded AIS B (Table 1) could have affected the level of trunk control 50 and hence contributed to the different standing ability. This speculation, however, needs further investigation.…”
mentioning
confidence: 99%
“…At the same time, the knee joint has to bear a greater force, and sometimes the local part will suddenly be subjected to a greater impact force, especially when the knee joint is in a physiological and anatomical weakness. These huge impact forces will cause instantaneous damage to the knee joint or the strain of the adjacent structures around the knee joint (Wang Y J, Li J J, Zhou H J, et al 2016) [2]. The mechanism of knee joint is very complex, and the treatment and recovery after injury is a big problem.…”
Section: Ntroductionmentioning
confidence: 99%